Research on relationship between energy consumption and GDP in Kazakhstan - Xuan Zhai; Jappar Juman; Aiymzhan Tulegenovna Makulova; Assel Valitkhanovna Khamzayeva; Binghan Du (Economies, 2024)
The relationship between energy consumption and economic development is one of the primary indicators for elaborating energy policies. Different countries are at different stages of economic development and have different levels of energy consumption. Since independence, Kazakhstan's economic development has gone through three stages: the unstable stage (1992-2000), the stage of rapid development (2001-2013), and the stage of stable development (2014-present). Kazakhstan's economy is shifting from an industry-led economy to a service-led economy, thus, the relationship between energy consumption and economic growth also changes. By analyzing the data on energy consumption and GDP during 1992-2023, it was found that a 1% growth of GDP caused a 0.3972% growth of energy consumption in Kazakhstan on average. Due to the long period of economic influence on energy consumption, Kazakhstan could realize the adjustment of the energy consumption structure without affecting economic development by eliminating fossil energy subsidies, reducing taxes on projects for the development of renewable energy, and increasing energy-saving facilities.
Keywords: 330; economic growth; Kazakhstan; elasticity coefficient; energy consumption; energy structure